Norman Y. Mineta and Susanne B. Wilson - Martin & Rita Rowe (photographic studio):::Creator::::::::::::
Photograph shows Mayor Norman Y. Mineta and Susanne B. Wilson looking at a YWCA pamphlet at San Jose City Hall.